Connection of translation with different fields (Journal of Science-Innovative Research in Uzbekistan, 2023)
Translation serves as a vital link between various fields, including Linguistics, Literature, History and Cultural Studies, and Science and Technology. This article examines the interdisciplinary nature of translation, examining its connections with linguistics, cultural studies, computer science, literature,and international relations It highlights the contributions of these disciplines to translations theory and practice, emphasizing the significance of collaboration and cross- disciplinary approaches. In Linguistics, translation acts as the foundation of understanding language structures, facilitating the analysis and comparison of different languages. In Literature, translation opens doors to new worlds of words, enabling the dissemination and appreciation of literary works across cultures. History and Cultural Studies benefit from translation by making historical documents and cultural texts available to scholars and enthusiasts worldwide, fostering cross-cultural understanding and enriching research endeavors. Lastly, in the realm of Science and Technology, translation plays a crucial role in disseminating scientific discoveries and technical information globally. The connection between translation and these diverse fields highlights its indispensable role in promoting cultural exchange, knowledge sharing, and global understanding.